Characteristics, comparisons and outcomes of COVID-19 hospitalization and mortality in the obstetric and non-obstetric population: Cohort study (Research, Society and Development, 2024)
Objective: To explore the impact of COVID-19 on morbidity and mortality among pregnant, postpartum and non-pregnant women hospitalized in Brazil. Method: This is a retrospective cohort study using data from the Brazilian Epidemiological Surveillance Information System (SIVEP-Gripe), covering epidemiological weeks from December 29, 2019 to January 2, 2021.Data were collected through the Brazilian SIVEP-Gripe; these data include sociodemographic aspects, comorbidities and other outcomes derived from hospitalization. Results: 40,640 hospitalized women aged between 10 and 49 years were categorized as pregnant (n=3,372), puerperal (n=794) and non-pregnant (n=36,474). The 19.3% of non-pregnant and non-postpartum women had no associated comorbidities, compared to 57.7% of pregnant women and 73.3% of postpartum women. There was an increased risk of oxygen saturation below 95% in postpartum women compared to pregnant women. Conclusion: Similarly, a higher risk of mortality was observed in postpartum women compared to pregnant women. There were no differences in the risk of morbidity and mortality associated with COVID-19 between non-pregnant and pregnant women.